Characterization of Disseminated Tumor Cells (DTCs) in Patients with Triple-Negative Breast Cancer (TNBC) - Anne Eckardt; Ivonne Nel; Laura Weydandt; Elisa Brochwitz; Anne Kathrin Höhn; Karsten Winter; Bahriye Aktas (Cells)
Triple negative breast cancer (TNBC) is the most aggressive molecular subtype and it lacks targetable receptors. Patients have an increased risk of recurrence and poor prognosis. Little is known concerning the characteristics of disseminated tumor cells (DTCs) and their role in TNBC patients. We analyzed the bone marrow aspirates of 80 patients with primary (n = 67) or recurrent (n = 13) TNBC, using a multi-parameter immunofluorescence staining procedure, including Pan-CK as an epithelial marker, vimentin (vim) as a marker of epithelial–mesenchymal transition, Ki67 for cell proliferation, and HER2 as well as PD-L1 as therapy-related markers. The DTC positive rate was 56% (n= 45) among the cohort. We found 20 different DTC subpopulations. The most frequently detected profile was CK+Vim+Ki67+ (n = 75 cells). The occurrence of CK- DTCs (n = 69) was significantly correlated to PD-L1 (r = −0.305, p < 0.01) and HER2 positivity (r = −0.234, p < 0.001). DTC positive patients that received neoadjuvant chemotherapy (NACT) and did not reach pathologic complete response were more likely to have CK- DTCs. Our data indicate that the occurrence of DTC subpopulations positive for Vim, Ki67, and HER2 appear to be markers for bad prognosis and could be therapeutically relevant. Furthermore, our results raise the question of whether DTCs are dormant in TNBC patients and persistent towards chemotherapy.